Makna Bersukacitalah Berdasarkan Filipi 4:4-7 Dan Refleksi Teologisnya Terhadap Orang Kristen Masa Kini - Enjela Estefani Manurung (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This research aims to describe the meaning of rejoice contained in Philippians 4:4-7 and reflect it on the lives of Christians today. In this writing, a qualitative method is used with an exegetical approach to draw meaning through the images that Paul has given through his writing, then the results of the interpretation and conclusions are expected to provide the right understanding for believers. The initial understanding of Christians assumes that if everything goes according to what is desired, it is desirable that they will rejoice and Christians imagine that joy is living without problems or just having fun and measuring this joy only by the amount of material things. The results of the analysis show that rejoicing cannot be separated from all His advice and rules and rejoicing is not just having fun or living without problems, but rejoicing in every situation of abundance, lack, then all things can be borne in Him who gives strength ( Phil. 4:13). Where the meaning of rejoice is expressed by being grateful in all circumstances, meaning both in hardship and happiness, disappointment, trials, suffering, which is implemented through friendly, kind-hearted actions towards everyone regardless of whether they are rich or poor and there is no place to worry and give up. everything to God by praying. So in this way, Christians who can do this will receive grace from God, namely God's peace which preserves and protects human hearts and minds, where disappointments, trials and suffering will be transformed by God into salvation. This research concludes that the meaning of rejoice is a command written by Paul for every Christian which can be seen from his gratitude and is implemented through actions that are friendly, kind to others and that there is no room for excessive worry and prayer. So that in the end you will obtain God's peace and God, the source of peace, will guard the hearts and minds of believers.